Fundusze odpowiedzialne jako przykład realizacji koncepcji zrównoważonego rozwoju przez instytucje finansowe - Ciechelska, Agnieszka (Socially Responsible Investments as an Example of Sustainable Development Realization in Financial Institutions, 2007)
Constantly growing world production makes natural sources become impoverished. In consequence the economic development can be seen as negative. This is one of the reasons why for many people not only more money and goods but also social and environmental aspects of high life quality play a very important role. This is the fundamental reason to create investment funds, which single out ethical enterprises in its investment portfolio. Such socially responsible investments have been developed since the seventy's having some stages. Currently the socially responsible investments share in the investments market is inappreciable. Funds, stimulated by their investors, can put pressure on enterprises to behave according to investors' expectations. For the investor investing in such funds it may have not only ethical values but can render comparable or higher profits like in traditional funds as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 107-117